2015
DOI: 10.3390/v7031391
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CMV-IgG Positivity of Donors Is Beneficial for alloHSCT Recipients with Respect to the Better Short-Term Immunological Recovery and High Level of CD4+CD25high Lymphocytes

Abstract: Hematopoietic stem cell transplantation from anti-cytomegalovirus immunoglobulin G (anti-CMV-IgG) positive donors facilitated immunological recovery post-transplant, which may indicate that chronic CMV infection has an effect on the immune system. This can be seen in the recipients after reconstitution with donor lymphocytes. We evaluated the composition of lymphocytes at hematologic recovery in 99 patients with hematologic malignancies post hematopoietic stem cell transplantation (HSCT). Anti-CMV-IgG seroposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 72 publications
1
21
0
Order By: Relevance
“…The latest observation shows beneficial role of CMV: overall effect of early CMV reactivation in the combined cohort was a 53% decrease in the risk of AML relapse by day 100 [31], but interestingly the effect appeared to be independent of CMV viral load, acute graft-versus-host disease or ganciclovir-associated neutropenia. Such observations as well as the analysis from our center show that CMV-positive donors facilitated immunological posttransplant recovery [7]. The case report with CMV-positive recipient and CMV-negative donor indicates that chronic CMV infection affects the immune system.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The latest observation shows beneficial role of CMV: overall effect of early CMV reactivation in the combined cohort was a 53% decrease in the risk of AML relapse by day 100 [31], but interestingly the effect appeared to be independent of CMV viral load, acute graft-versus-host disease or ganciclovir-associated neutropenia. Such observations as well as the analysis from our center show that CMV-positive donors facilitated immunological posttransplant recovery [7]. The case report with CMV-positive recipient and CMV-negative donor indicates that chronic CMV infection affects the immune system.…”
Section: Discussionsupporting
confidence: 63%
“…On the other hand, CMV may cause a serious disease in severe immunosuppressive patients for example with highly developed AIDS, after HSCT, when CD4+ T helper cells are below 100/µl. In solid organ transplant and in stem cell transplant, the impact of the cytomegalovirus (CMV) serologic status can play a significant role in the outcome [7]. However, the issue on the effect of the donors anti-cytomegalovirus immunoglobulin G (CMV-IgG) seronegativity on the immune system and overall survival is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…It signals to the T cell via binding to the IL-2 receptor, a complex consisting of three chains, termed α (CD25), β (CD122), and γ (CD132) (Liao et al, 2011). Increased risk of HCMV reactivation is associated with reduced numbers of CD4+CD25 high cells, and a study of 99 HSCT recipients found that numbers of CD4+CD25 high but not CD4+ T cells was an independent factor for risk of CMV reactivation (Jaskula et al, 2015). The expression of other functional markers on HCMV specific CD4+ T cells have also been studied in HSCT and SOT patients.…”
Section: Surface Markers Of Hcmv-specific Cd4+ T Cells In Hsct Recipimentioning
confidence: 99%
“…Sometimes CMV plays a crucial role in the immune response and inflammatory stimulation: it prompts lymphoproliferative disease [7] or a cross-reactive immune response and graft-versus-host reaction [8]. The impact of CMV serologic status can play a significant role in the outcome of hematopoietic stem cell transplantation (HSCT) [9]. Unfortunately, such CMV-IgG serostatus is interpreted as a qualitative parameter only [6,9] and in the context of its influence on final outcome [5,6].…”
Section: Introductionmentioning
confidence: 99%